Reflective Judgement: Understanding Entrepreneurship as Ethical Practice - Clarke, Jean (Journal of business ethics, 2010)
Recently, the ethical rather than just the economic resonance of entrepreneurship has attracted attention with researchers highlighting entrepreneurship and ethics as interwoven processes of value creation and management. Recognising that traditional normative perspectives on ethics are limited in application in entrepreneurial contexts, this stream of research has theorised entrepreneurship and ethics as the pragmatic production of useful effects through the alignment of public–private values. In this article, we critique this view and use Kant’s concept of reflective judgement as discussed in his Critique of the Power of Judgement to theorise ethical entrepreneurial practice as the capacity to routinely break free from current conventions through the imaginative creation and use of self-legislating maxims. Through an analysis of the narratives of 12 entrepreneurs, we suggest there are three dimensions to reflective judgement in entrepreneurial contexts: (1) Social Performance; (2) Public Challenge and; (3) Personal Autonomy. Whilst the entrepreneurs were alive to the importance of commercial return, their narratives demonstrated further concern for, and commitment to, standards that they rationally and imaginatively felt as being appropriate. In our discussion, we integrate the findings into existing theoretical categories from entrepreneurship studies to better appreciate ethics within the context of value creation.